2009
DOI: 10.1177/1938640009342894
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Spartathlon Ultramarathon Race on Athletes' Plantar Pressure Patterns

Abstract: More than 90% of injuries in runners are recorded in the lower extremity, equally affecting the regions of the knee, shank, and foot. Stress fractures are responsible for numerous running-related injuries. In the current study, the plantar pressure patterns of prerace, immediately postrace, and 24 hours after long-distance running in the Spartathlon were analyzed to compare foot loading in the respective conditions. Forty-six male participants of the Spartathlon ultramarathon were examined before, immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
0
19
0
3
Order By: Relevance
“…The increased loading in forefoot of 10 km runners may also suggest attention for training, as this pattern of loading can influence the development of patellofemoral pain syndrome 16 , which depends on the running technique 17 , and is a risk factor for ankle injuries such as ankle sprains 18 . Considering a regular involvement in running training, the persistence of changes after competition (up to 24 h after a prolonged running 19 ) suggest further attention to the foot health among athletes and coaches.…”
Section: Discussionmentioning
confidence: 99%
“…The increased loading in forefoot of 10 km runners may also suggest attention for training, as this pattern of loading can influence the development of patellofemoral pain syndrome 16 , which depends on the running technique 17 , and is a risk factor for ankle injuries such as ankle sprains 18 . Considering a regular involvement in running training, the persistence of changes after competition (up to 24 h after a prolonged running 19 ) suggest further attention to the foot health among athletes and coaches.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with biomechanical studies assessing the foot plantar pressure before and after long-distance running. These studies found that the loading under the 4 th and 5 th metatarsals and the heel were significantly increased [40][41][42]. Thijs et al [43] also reported that the greater plantar pressure under the metatarsals and lateral heel regions can be related to patellofemoral pain in runners.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with the peak pressure, the impulse is a more sensitive indicator of the etiology of foot injury; it also has a higher association with pain or injury (Hodge, Bath, & Carter, 1999) and has greater differentiability when comparing the perceived comfort (Chen, Nigg, & De Koning, 1994). Various surveys have investigated the potential causative factors of stress fractures, several of which were attributed to the excessive plantar loading during landing (Karagounis et al, 2009;Mizrahi, Verbitskya, Isakov, & Daily, 2000). These surveys showed that excessive plantar loading poses additional risks to bone integrity.…”
Section: Discussionmentioning
confidence: 97%
“…This study proved that functional insoles significantly reduce the peak pressures in the hallux, MPJs 1 to 4, and heels, all of which are vulnerable to injuries (Werner, Gell, Hartigan, Wiggerman, & Keyserling, 2010). Furthermore, repetitive submaximal stimuli can reduce the individual loading capacity of the bone and lead to structural changes in the areas of maximal stress (Karagounis et al, 2009). After a long period of repeated foot loading, the plantar load is transferred from the toes to the MPJs and causes higher peak pressures in the MPJs compared with that at the start of walking or running; this repeated loading may lead to stress fractures in the MPJ bones, particularly in the second and third MPJs, which are vulnerable because of the discrepancy between the bone strength and imposed plantar pressure (Karagounis et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation